Implementation of The Economic Order Quantity Method For Inventory of Goods - Muhammad Iqbal Kusrachmansyah; Erni Seniwati; Acihmah Sidauruk (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
The inventory system that is being carried out at this time is by manual method where the inventory is still made using Microsoft Office in the form of Microsoft Word and Microsoft Excel in which data is written about data on the presentation of basic food items sold, expenditure of goods and orders. However, the presentation of goods is less efficient and effective. By looking at this situation and condition, the author makes a system